Technická analýza - Krčová, Vendula (Vysoké učení technické v Brně. Fakulta podnikatelská, 2012)
Tato diplomová práce se zabývá obecnou charakteristikou technické analýzy, vymezením informačních zdrojů a přístupům k technické analýze. Zvláštní pozornost je věnována jednotlivým indikátorům technické analýzy. Praktická část představuje aplikaci vybraných indikátorů při hodnocení situace na měnovém trhu.

This diploma thesis is focused on the general characteristics of the technical analysis, definitions of the information sources and technical analyses. Main attention is given to the particular indicators of the technical analysis. Practical part of this thesis includes applying of the defined indicators in the evaluation of the money market situation.
Technical Analysis
Keywords: technická analýza; trend; trendové indikátory; momentové indikátory; klouzavý průměr; trading; Forex; oscilátory; indikátory volatility.; technical analysis; trend; trend indicators; torque indicators; moving average; trading; Forex; oscillators; indicators of volatility